Structuring the situation: Organizational goals trigger and direct decision-making - Greve, Henrich R. (Frontiers in Psychology, 2023)
Organizational goals are assigned to individuals, and thus differ from goals that individuals voluntarily adopt. The Carnegie School has a significant research stream on how organizations are affected by goals, with a focus on how performance shortfalls disrupt regular organizational behavior and trigger a search for alternative actions. The theory is founded on organizational satisficing through comparing performance on each goal variable with an aspiration level that is updated through historical and peer comparison. Performance shortfalls can trigger search, which in turn is directed towards specific problems and concluded once a sufficiently good alternative is found. Current research gives a good understanding of the organization-level process of setting aspiration levels, triggering search for alternatives, and making decisions, but the individual level mechanisms contributing to it are less well known. An assessment of the progress of Carnegie School research so far reveals a list of research questions that should be resolved in order to understand the behavior of individuals who are assigned organizational goals. We need to understand how individual updating of aspiration levels, triggering of search, directing of search, and decision-making help explain organizational responses to goals. The role of construal, or interpretation, in guiding these processes is a central theoretical mechanism that needs further investigation. Research using the experimental method to capture these processes is especially welcome because it is currently scarce.